2000
DOI: 10.1046/j.1365-2249.2000.01330.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity in ulcerative colitis (UC): a predominant colonic mucosal B cell response against human tropomyosin isoform 5

Abstract: SUMMARYWe set out to examine if the IgG-producing cells in the colonic mucosa in UC are committed to tropomyosin isoform 5 (hTM5), a putative autoantigen in UC. Lamina propria mononuclear cells (LPMC) were isolated from colonoscopic biopsy specimens from recto-sigmoid and proximal colon. Twenty-three patients with UC, eight with Crohn's colitis (CC), and 10 non-inflammatory bowel disease (non-IBD) controls were included. The ELISPOT assays were used to quantify lamina propria B cells producing total immunoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 32 publications
0
32
0
2
Order By: Relevance
“…However, the titers of antineutrophil antibodies do not seem to correlate with disease activity in UC (98), and their biological significance in UC patients is unclear. Levels of antibodies against a human intestinal tropomyosin isoform also have been reported to be increased in UC patients in some studies (63,82). In addition, activated complement factors have been noted to colocalize with anticolon antibodies on the luminal surface of the epithelium (70).…”
Section: Autoimmune Diseasementioning
confidence: 98%
See 1 more Smart Citation
“…However, the titers of antineutrophil antibodies do not seem to correlate with disease activity in UC (98), and their biological significance in UC patients is unclear. Levels of antibodies against a human intestinal tropomyosin isoform also have been reported to be increased in UC patients in some studies (63,82). In addition, activated complement factors have been noted to colocalize with anticolon antibodies on the luminal surface of the epithelium (70).…”
Section: Autoimmune Diseasementioning
confidence: 98%
“…A destructive inflammatory response directed toward a selfantigen such as mucin, goblet cells, colonocytes, or other cells has been proposed as the underlying basis of IBD, particularly in regards to UC (28,46,63,82). As noted above, antibodies against neutrophils have been found in many but not all UC patients (13,63,70,81).…”
Section: Autoimmune Diseasementioning
confidence: 99%
“…Th2 predominance has been suggested in the pathogenesis of UC. 24 -27 Generation of autoantibodies to tropomyosin 28 and perinuclear anti-neutrophil antibodies (p-ANCA) 29 is a characteristic humoral immune response in patients with UC. The number of LPL B cells producing anti-tropomyosin isoform 5 antibodies has been found to be significantly higher in UC than in CD patients and controls.…”
Section: Inflamm Bowel Dismentioning
confidence: 99%
“…The number of LPL B cells producing anti-tropomyosin isoform 5 antibodies has been found to be significantly higher in UC than in CD patients and controls. 28 Differences in antibody production in colonic LPL in patients with UC suggest the existence of abnormal humoral immune responses in mucosal B cells of UC. It is of great interest that increased proliferation of CD19ϩCD138ϩ cells was observed in pouchitis mucosa with UC.…”
Section: Inflamm Bowel Dismentioning
confidence: 99%
“…hTM isoform 5 (hTM5) is the predominant isoform in normal colon epithelium and it acts as an autoantigen in ulcerative colitis (UC) Geng et al 1998). We and others have shown that patients with UC demonstrate both humoral and cellular immune responses against hTM, particularly against isoform 5 (hTM5) Geng et al 1998;Onuma et al, 2000;Biancone et al, 1995 ;Sakamaki et al, 2000 ;Taniguchi et al, 2001). A K-ras mutation occurs relatively early in human carcinogenesis (Vogelstein et al, 1988), and it is detected in various types of human malignancies (Soh et al, 1993;Cooper 1995).…”
Section: Introductionmentioning
confidence: 99%